2017
DOI: 10.1155/2017/8064613
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Genetic Diversity of COX-III Gene in Lowland Chickens and Tibetan Chickens

Abstract: To obtain a full understanding of the genetic diversity of the cytochrome oxidase III gene (COX-III) and its association with high altitude adaptation in Tibetan chickens, we sequenced COX-III in 12 chicken populations (155 Tibetan chickens and 145 other domestic chickens). We identified a total of 11 single nucleotide polymorphisms (SNPs) and 12 haplotypes (Ha1–Ha12). Low genetic diversity (haplotype diversity = 0.531 ± 0.087, nucleotide diversity = 0.00125) was detected for COX-III, and haplotype diversity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The genetic distance was conducted using Kimura 2-parameter method and phylogenic analyses based on COX-III sequence data were conducted by neighbor-joining (NJ) using MEGA program version 7.0. [10]. Bootstrap method for genetic distance analysis was conducted with 1000 replicates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic distance was conducted using Kimura 2-parameter method and phylogenic analyses based on COX-III sequence data were conducted by neighbor-joining (NJ) using MEGA program version 7.0. [10]. Bootstrap method for genetic distance analysis was conducted with 1000 replicates.…”
Section: Methodsmentioning
confidence: 99%
“…The COX subunit III protein is an important element for regulating the efficiency of proton translocation in cytochrome oxidase over several turnovers [8]. COX subunit III has been used in several genetic diversity studies including human [9], chicken [10], brown seaweed [11], and Babesia [12]. The function of COX-III gene is very important for the respiratory chain and is highly conserved among species [10].…”
Section: Introductionmentioning
confidence: 99%
“…This result showed similar status to a previous study of eight Sichuan indigenous chicken breeds based on microsatellite analysis. Meanwhile, the haplotype and nucleotide diversity from CK, LN, JY, EM and MC population were higher than the results of Liu et al, (2017). These results were caused by different researched regions of mtDNA sequence and methods.…”
Section: Discussionmentioning
confidence: 72%
“…A high genetic difference were observed between these nine chicken breeds which showed a pattern similar to that obtained in the previous investigation of Chinese local chicken populations (Liu et al 2006) The value of average number of nucleotide differences is higher (0.016) in Dulong chicken than other Sichuan local chicken breeds (0.007-0.015) suggested that those sequences are potentially isolated from other chickens. Compared with genetic diversity study of COX-III gene in lowland (Muchuan, Emei, Jiuyuan, and Tianfu) and Tibetan chickens (Liu et al 2017), and the study of nuclear gene bitter taste receptor gene family in Sichuan domestic and Tibetan chicken populations (Su et al 2016), the control region showed extensive genetic diversity (average number of nucleotide difference (K) ranged from 3.167 to 7.730) than COX-III gene (K ranged from 0.720 to 1.621) and Tas2rs (0.344-3.564). A high level of diversity makes control region particularly useful for detecting population genetic structure at the intraspecific level.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with genetic diversity study of COX-III gene in lowland (Muchuan, Emei, Jiuyuan, and Tianfu) and Tibetan chickens (Liu et al. 2017 ), and the study of nuclear gene bitter taste receptor gene family in Sichuan domestic and Tibetan chicken populations (Su et al. 2016 ), the control region showed extensive genetic diversity (average number of nucleotide difference ( K ) ranged from 3.167 to 7.730) than COX-III gene ( K ranged from 0.720 to 1.621) and Tas2rs (0.344–3.564).…”
Section: Discussionmentioning
confidence: 99%